A Unique Case of Conjuctival Choristoma Masquerading As Nasal Pterygium - Mukta Sharma; Shruti Anand (Delhi Journal of Ophthalmology)
Being at the distinctive position of covering the eye ball, conjunctiva is frequently involved in array of local and systemic disorders. Tumors of cornea and conjunctiva often present the ophthalmologist with a difficult diagnostic and therapeutic challenge Histopathology findings force us to revisit our diagnosis. With this background we present our distinctive case of conjunctival cyst which extended to the cornea and gave the appearance of a pterygium Choristoma which masqueraded itself as inflamed pterygium makes it one of the very rare cases to be reported. It is suggested that dermoid choristoma should be included in the differential diagnosis of lower eyelid masses.